2017
DOI: 10.1074/jbc.m117.789495
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle electron microscopy structure of UDP-glucose:glycoprotein glucosyltransferase suggests a selectivity mechanism for misfolded proteins

Abstract: The enzyme UDP-glucose:glycoprotein glucosyltransferase (UGGT) mediates quality control of glycoproteins in the endoplasmic reticulum by attaching glucose to N-linked glycan of misfolded proteins. As a sensor, UGGT ensures that misfolded proteins are recognized by the lectin chaperones and do not leave the secretory pathway. The structure of UGGT and the mechanism of its selectivity for misfolded proteins have been unknown for 25 years. Here, we used negative-stain electron microscopy and small-angle X-ray sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 51 publications
1
29
1
Order By: Relevance
“…Only correctly folded glycoproteins escape UGGT-mediated reglucosylation and can progress down the secretory pathway -to the Golgi and beyond. More than 25 years after the discovery of UGGT [3], recent structural and functional work has uncovered the protein's multi-domain architecture and obtained preliminary evidence of its inter-domain conformational flexibility [4][5][6]. Negativestain electron microscopy and small-angle X-ray scattering (SAXS) first revealed an arc-like structure with some degree of structural variability [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only correctly folded glycoproteins escape UGGT-mediated reglucosylation and can progress down the secretory pathway -to the Golgi and beyond. More than 25 years after the discovery of UGGT [3], recent structural and functional work has uncovered the protein's multi-domain architecture and obtained preliminary evidence of its inter-domain conformational flexibility [4][5][6]. Negativestain electron microscopy and small-angle X-ray scattering (SAXS) first revealed an arc-like structure with some degree of structural variability [4].…”
Section: Introductionmentioning
confidence: 99%
“…More than 25 years after the discovery of UGGT [3], recent structural and functional work has uncovered the protein's multi-domain architecture and obtained preliminary evidence of its inter-domain conformational flexibility [4][5][6]. Negativestain electron microscopy and small-angle X-ray scattering (SAXS) first revealed an arc-like structure with some degree of structural variability [4]. Soon after, four distinct full length Chaetomium thermophilum UGGT (CtUGGT) crystal structures, together with a 15 Å cryo-EM reconstruction of the same protein, suggested that the C-terminal portion -comprising two β-sandwiches and the catalytic domainconstitutes a relatively rigid structure, while most of the conformational flexibility localizes to the four N-terminal thioredoxin-like (TRXL) domains [5].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of any obvious sequence homology of this portion of UGGT with proteins of known fold led to the creation of a UGGT‐specific protein fold family (Pfam family PF06427) which gathers all known eukaryotic UGGT N‐terminal sequences. The most recent secondary structure and domain boundary predictions for UGGT detected three thioredoxin‐like (TRXL) domains in this region . The canonical TRXL fold (Pfam family PF13848) comprises a thioredoxin fold (a four‐stranded β sheet sandwiched between three α‐ helices, TRX=βαβ − αββα Pfam family PF00085, red in Figure ), modified by the insertion of a 4‐helix subdomain (TRXL=βαβ − αααα − αββα blue in Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…86,87 Asparagine-, isoleucineand phenylalanine-ladders are found in the core of each monomer, stabilizing the basic b-helical architecture of the monomer. The asparagine ladder (residues 193, 214, 248, and 291) is located right at the T1 turn, while the isoleucine (residues 68, 98, 134, 167, 311, 357) and phenylalanine (residues 103,139,172,195) ladders are found in the PB1 and PB2 sheets, respectively. A ladder containing isoleucines and a leucine (Ile84, Ile147, Ile179 and Leu125) is present in the PB3 sheet.…”
Section: Van Raaijmentioning
confidence: 99%
See 1 more Smart Citation